Inconsistent intraspecific pattern in leaf life span along nitrogen‐supply gradient. Issue 2 (15th February 2017) - Oikawa, Shimpei; Suno, Koya; Osada, Noriyuki
Abstract : PREMISE OF THE STUDY: Leaf life span (LLS) has long been hypothesized to plastically increase with decreasing nitrogen (N) supply from soil to maximize N retention, carbon assimilation, and fitness; however, accumulating evidence shows no consistent trend. The apparent inconsistencies are explained by a recent model that assumes LLS has a hump‐shaped quadratic response to the N‐supply gradient. The available evidence mostly originates from comparisons of LLS at only two levels of N availability, and the hypothesis remains unanswered. METHODS: We investigated LLS of two asteraceous forbs ( Adenocaulon himalaicum and Xanthium canadense ) experimentally grown at eight levels of N supply, which covered a range of N supply in their natural habitats. We additionally conducted a literature search to retrieve studies reporting LLS response along an N‐supply gradient. KEY RESULTS: The LLS of neither species showed a hump‐shaped response along the N‐supply gradient. Past studies examining the LLS of an aquatic forb and terrestrial shrubs and trees along the N‐supply gradient (more than four levels of N supply) also refuted the hypothesis. CONCLUSIONS: The LLS of a single species exhibited neither an increase nor a hump‐shaped response to decreased N supply in a variety of life forms. Comparisons at only a few N levels are misleading with regard to LLS response to N supply.